1991
DOI: 10.1021/om00047a066
|View full text |Cite
|
Sign up to set email alerts
|

Multiple bonds between main-group elements and transition metals. 77. Condensation reactions of methyltrioxorhenium(VII) with catechols and aromatic thiols

Abstract: strengthens the Os-carbonyl bond opposite the donor atom (Rh). This effect has been observed previously in related dative-bonded c o m p o~n d s .~~~~~~~The Rh-Os separation of 2.8744 (3) 8, is typical of a single bond but is not a useful indication about the nature of this interaction, especially in the presence of the bridging alkyne. This Rh-Os bond is somewhat longer than that observed (2.758 (5) 8,) in the related compound [RhOsC1zBr(p-CO)(dppm)2] ,53 which in our interpretation would have an Os-Rh donor-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

1991
1991
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 0 publications
0
39
0
Order By: Relevance
“…Among the various ways to prepare rhenium diolates, the condensation of an oxorhenium complex and a neutral diol molecule (Scheme 2) is particularly relevant for the catalytic process so this will be the main focus here. Apart from the condensation of CH 3 ReO 3 and o-catechol (a diol incapable of undergoing DODH), [35,36] this reaction was first employed by Herrmann and co-workers in 1991 for the preparation of the light-yellow CH 3 ReO 2 (pinacolate) in CH 2 Cl 2 . [37] The reversibility of the condensation was later demonstrated for the analogues CH 3 ReO 2 (perfluoropinacolate).…”
Section: Formation Of Rhenium Diolatesmentioning
confidence: 99%
“…Among the various ways to prepare rhenium diolates, the condensation of an oxorhenium complex and a neutral diol molecule (Scheme 2) is particularly relevant for the catalytic process so this will be the main focus here. Apart from the condensation of CH 3 ReO 3 and o-catechol (a diol incapable of undergoing DODH), [35,36] this reaction was first employed by Herrmann and co-workers in 1991 for the preparation of the light-yellow CH 3 ReO 2 (pinacolate) in CH 2 Cl 2 . [37] The reversibility of the condensation was later demonstrated for the analogues CH 3 ReO 2 (perfluoropinacolate).…”
Section: Formation Of Rhenium Diolatesmentioning
confidence: 99%
“…[27] had previously demonstrated oxo-abstraction of Cp*ReO­ 3 by phosphines to form the oxo-bridged dimeric rhenium species (Cp*) 2 Re 2 O 4 . Condensation between methyltrioxorheynium (MTO) and catechols had also been previously demonstrated [28]. Finally, Gable [29] had independently synthesized reduced Cp*ReO(diolate) species and found that upon heating, the diolate undergoes cycloreversion to form alkene and Cp*ReO 3 , successfully demonstrating the final step of the DODH reaction several years before the report of the catalytic reaction.…”
Section: Reduction Mechanism: Oxo-abstractionmentioning
confidence: 97%
“…58 Other reactions that result in reduction o f (12) have been reported; for example, ZnMe 2 reacts to give [{Re(u-O)(O)Me 2 } J 44 ' 45 and polymer-bound triphenylphosphine removes an oxo ligand to form "ReO 2 Me" in situ, which can then be captured by a l k y n e 1 1 * 2 6 (Scheme 3) or reoxidized with phenanthrenequinone to give (14). 20 Ethylene glycol and pinacol react with (12) in methanol to give rhenium(VI) oxo-bridged compounds but reactions with pinacol or perfluoropinacol in CH 2 C1 2 give rhenium(VII) (IS). 5 0 * 5 9 A related water elimination reaction forms (16) in Scheme 6.…”
Section: Compoundmentioning
confidence: 99%
“…[RetNR^CTOR'jR 3 ] (R'=Bu l or Xyl, R 2 = Bu\ R 3 = CH 2 Bu l ; R'=Xyl, R 2 = CMe 2 Ph, R 3 = CH 2 CMe 2 Ph) complexes react with sources of H C 1 to yield chloro alkylidene-alkylidyne compounds (e.g., (20) via Equation (io)). 75 ' 76 ' 78 ' 79 Remarkably, the reaction in Equation (10) can even be carried out in air using aqueous HC1, illustrating the stability of the alkylidene and alkylidyne ligands in (20).…”
Section: Rhenium(vii)mentioning
confidence: 99%
See 1 more Smart Citation